The evolution of protoplanetary disks in the arches cluster - Olczak, Christoph (The astrophysical journal, 2012)
Most stars form in a cluster environment. These stars are initially surrounded by disks from which potentially planetary systems form. Of all cluster environments, starburst clusters are probably the most hostile for planetary systems in our Galaxy. The intense stellar radiation and extreme density favor rapid destruction of circumstellar disks via photoevaporation and stellar encounters. Evolving a virialized model of the Arches cluster in the Galactic tidal field, we investigate the effect of stellar encounters on circumstellar disks in a prototypical starburst cluster. Despite its proximity to the deep gravitational potential of the Galactic center, only a moderate fraction of members escapes to form an extended pair of tidal tails. Our simulations show that encounters destroy one-third of the circumstellar disks in the cluster core within the first 2.5 Myr of evolution, preferentially affecting the least and most massive stars. A small fraction of these events causes rapid ejection and the formation of a weaker second pair of tidal tails that is overpopulated by disk-poor stars. Two predictions arise from our study. (1) If not destroyed by photoevaporation protoplanetary disks of massive late B- and early O-type stars represent the most likely hosts of planet formation in starburst clusters. (2) Multi-epoch K - and L -band photometry of the Arches cluster would provide the kinematically selected membership sample required to detect the additional pair of disk-poor tidal tails.